Pengaruh Game Based Learning terhadap Hasil Belajar Matematika Siswa SD - Pangestu, Yoga; Amri, Mira Amelia; Putra, Adi (Papanda, 2025)
This study aims to analyze the effect of Game Based Learning (GBL) on mathematics learning outcomes of elementary school students through a literature review. The process in the literature study method begins with searching for relevant references through platforms such as Google Scholar. After that, the various sources found are grouped according to the formulation of the research problem that has been determined previously. The next step was to analyze the information collected to identify important findings related to the impact of Game-Based Learning (GBL). Finally, the results of the analysis were interpreted to draw conclusions that could answer the research objectives. Data was obtained from accredited journals of the last five years. Therefore, by using a qualitative approach, this study was able to find facts analytically about the effect of game-based learning on student learning outcomes. The results showed that GBL through various platforms such as Kahoot, Quizziz, Bamboozle, Educandy and Wordwall proved effective in improving students' learning outcomes, motivation and comprehension. This study supports the use of GBL as an innovative strategy in mathematics learning.